DEPRESSION AND CARDIAC DISEASES (REVIEW OF LITERATURE) - E. V. Vinokurov (Scientific Сentre for Family Health and Human Reproduction Problems, 2017)
The article deals with the important problem in the field of consultative psychiatry - comorbid depressive disorders in patients with cardiovascular diseases. Depression is highly prevalent in cardiac patients. Between 31-45 % of patients with coronary artery disease suffer from clinically significant depressive symptoms. Furthermore, 20 % of patients with coronary heart disease meet criteria for the major depressive disorder. Patients with heartfailure, atrial fibrillation and ones undergoing implantable cardioverter-defibrillator placement are similarly at increased risk for elevated depressive symptoms and for major depressive disorder. In patients with heart diseases, depression is chronic, persistent, and associated with worse health-related quality of life, recurrent cardiac events, and mortality. At present, pharmacologic and psychotherapeutic interventions appear to be safe and effective at reducing depressive symptoms in patients with cardiovascular diseases and may impact cardiac outcomes. Despite this, depression remains under-recognized and undertreated in patients at risk for or living with cardiovascular diseases. In this review, we summarize the evidence linking depression to increased risk of cardiovascular diseases and worse patient outcomes. The paper presents a review of the literature on epidemiology, comorbid conditions, and risk factors for depression in heart diseases. Future studies in this direction with involvement of cardiologists and psychiatrists should be held.